Location matters: Regional variation in association of community burden of COVID-19 with caregiver and youth worry. (September 2022) - Marshall, Andrew T.; Hackman, Daniel A.; Kan, Eric; Abad, Shermaine; Baker, Fiona C.; Baskin-Sommers, Arielle; Dowling, Gayathri J.; Gonzalez, Marybel R.; Guillaume, Mathieu; Kiss, Orsolya; McCabe, Connor J.; McCandliss, Bruce D.; et al.
Abstract: Our study characterized associations between three indicators of COVID-19's community-level impact in 20 geographically diverse metropolitan regions and how worried youth and their caregivers in the Adolescent Brain Cognitive Development℠ Study have been about COVID-19. County-level COVID-19 case/death rates and monthly unemployment rates were geocoded to participants' addresses. Caregivers' (vs. youths') COVID-19-related worry was more strongly associated with COVID-19's community impact, independent of sociodemographics and pre-pandemic anxiety levels, with these associations varying by location. Public-health agencies and healthcare providers should avoid adopting uniform "one-size-fits-all" approaches to addressing COVID-19-related emotional distress and must consider specific communities' needs, challenges, and strengths. Highlights: Different US regions have been differentially affected by the COVID-19 pandemic. COVID-19's county-level impact was geocoded to youth and caregiver addresses. COVID-19's impact was more strongly associated with caregivers' COVID-19-related worry. Associations were stronger if family members were at risk of COVID-19 exposure. Identifying communities most in need may effectively ease burdens on mental health and optimize risk communication.